Vascular access in a post-lung transplant patient on maintenance hemodialysis: a case report - Mariko Kawamura; Motonobu Nakamura; Ryo Matsuura; Motoki Odawara; Yu Kurata; Midori Sakashita; Daisuke Yamada; Yoshifumi Hamasaki; Chihiro Konoeda; Masaaki Sato; Haruki Kume; Masaomi Nangaku (Renal Replacement Therapy, 2024)
Abstract Background An arteriovenous fistula (AVF) is the most common type of vascular access for hemodialysis. As it causes volume overload and sometimes increases pulmonary artery pressure, it is unsuitable for some patients. Herein, we describe a patient with acute kidney disease who required maintenance hemodialysis with vascular access other than an AVF owing to post-lung transplant pulmonary hypertension. Case presentation A 50-year-old man with interstitial pneumonia underwent living-donor lobar lung transplantation at our hospital. Weaning from venoarterial extracorporeal membrane oxygenation was achieved; however, the patient required mechanical ventilation owing to pulmonary hypertension. He developed acute kidney disease and required maintenance hemodialysis with sustainable vascular access. Although echocardiography showed a normal ejection fraction, we expected volume overload after arteriovenous access construction to worsen his pulmonary hypertension because of his inadequate pulmonary vascular bed. Therefore, a tunneled central vein catheter was implanted into the right femoral vein as a bridge, and superficialization of the right brachial artery was performed for long-term vascular access. Conclusions As this patient had sustained post-transplant pulmonary hypertension and small grafts, we avoided creating arteriovenous access because of concern over the aggravation of pulmonary hypertension. Evaluation of right heart function and pulmonary hypertension is important before arteriovenous access construction.